Job search monitoring and assistance for the unemployed - Ioana E. Marinescu (IZA World of Labor, 2017)
In many countries, reducing unemployment is among the most important policy goals. In this context, monitoring job search by the unemployed and providing job search assistance can play a crucial role. However, more and more stringent monitoring and sanctions are not a panacea. Policymakers must consider possible downsides, such as unemployed people accepting less stable and lower-paying jobs. Tying “moderate” monitoring to job search assistance may be the essential ingredient to make this approach successful.
Keywords: J22; J64; J65; J68; 330; job search; unemployment; monitoring; counseling; assistance